Human occupations of mountain environments - Grimaldi, Stefano (2016)
This special issue of Quaternary International concerns the Human Occupations in Mountain Environments (hereafter HOME). This topic gives the name of one of the commissions of the International Union of Prehistoric and Protohistoric Science and it was also the topic discussed during the session A6a - organised by the HOME members - held during the last XVII IUPPS conference (Burgos, Spain, 1-7 september 2014). The papers here presented are the proceedings of that session. Here we present our point about mountain archaeology, including methodology and some future challenges.